The operational procedure of the Interior Troops and State Border Guard units in carrying out joint missions in a special operation to cease domestic armed conflict in the border area - Allerov, Yu. V.; Sutyushev, Т. А.; Morozov, І. Ye. (Honor and Law, 2019)
Issues of cooperation of the Interior Troops and State Border Guard units in a special-purpose operation at localization and neutralization of the domestic armed conflict in the border area are considered. The operational procedure of the Interior Troops and State Border Guard units in carrying out common tasks on isolating a special operation (SO) area, on searching frontier crossers and illegal armed formations, on overlapping (covering) and blocking particular directions of SO area, on information support of SO, and on clearing up SO area is given. The results of field tests and exercises in reference to the considered problems are given.